PENINGKATAN KEMAMPUAN PRODUKSI DAN MANAJERIAL UKM GENTENG DESA TAHUNAN KECAMATAN SALE SEBAGAI UPAYA MENGURANGI JUMLAH KEMISKINAN - Dian Ayu Liana Dewi; Maslichan Maslichan (Buletin Abdi Masyarakat, 2020)
This program to increase production and managerial capabilities of the UKM Genteng Tahunan village in Sale sub-district aims to increase productivity both in quantity and quality oftile products by utilizing business management development in order to be able to increase theincome and existence of these UKM in particular and be able to assist government programs inpoverty alleviation. The target of this program is to increase the ability and motivation of thebusiness, increase marketing capabilities and be able to separate business finance frompersonal finance by making simple finances. Activities that have been carried out in this serviceprogram are: 1) Training in marketing management strategies; 2) Training on marketingtechnology implementation 3) Training by implementing business administration and 4) simplefinancial management training. The output generated by this activity in addition to the aboveactivities is publicity in scientific journals.Keyword: service program, business management.